Volume Rendering of Dense B-Scan Optical Coherence Tomography Angiography to Evaluate the Connectivity of Macular Blood Flow - Cabral, Diogo; Pereira, Telmo; Ledesma-Gil, Gerardo; Rodrigues, Catarina; Coscas, Florence; Sarraf, David; Freund, K. Bailey (Investigative ophthalmology & visual science, 2020)
To characterize macular blood flow connectivity using volume rendering of dense B-scan (DB) optical coherence tomography angiography (OCTA) data. This was a prospective, cross-sectional, observational study. DB OCTA perifoveal scans were performed on healthy subjects using the Spectralis HRA+OCT2. A volumetric projection artifact removal algorithm and customized filters were applied to raw OCTA voxel data. Volume rendering was performed using a workflow on Imaris 9.5 software. Vascular graphs were obtained from angiographic data using the algorithm threshold-loops. Superficial arteries and veins were identified from color fundus photographs and connections between adjacent arteries and veins displayed using the shortest path algorithm. Connective pathway locations were analyzed with cross-sectional OCT and OCTA to determine their course through the superficial vascular complex (SVC) and the deep vascular complex (DVC). Fourteen eyes from seven subjects (mean age: 28 ± 5 years; 3 women) were included in this analysis. One hundred and twenty-six vascular connections were analyzed. In all cases, the shortest path connections between superficial arteries and veins coursed through the DVC. We did not identify shortest path connections confined to the SVC. Volumetric analysis of vascular connectivity supports a predominantly in-series arrangement of blood flow between the SVC and DVC within the human perifoveal macula.